PROGRAMAS ORÇAMENTÁRIOS AMBIENTAIS NAS CONTAS DE GESTÃO NO TRIBUNAL DE CONTAS DE MATO GROSSO DO SUL - Daniela Marques Caramalac (2023)
The public budget is an instrument for planning the application of the state's financial resources to implement public policies, including public policies aimed at sustainability and the environment. This work examines how the Mato Grosso do Sul Court of Auditors monitors the execution of the state budget along with the accountability of the management units that carry out the state's environmental management. After identifying how the multi-year budgetary (2016-2019) addressed the environmental issue, the volume of financial resources that was applied to budgetary actions was analyzed. Exploratory, descriptive, transversal and quantitative research was carried out, with bibliographic and documentary research. The study found a low rate of resource application in the budgetary actions analyzed and a lack of detailed data that allows visualization of the results of the application of resources. The management report, inspired by the integrated report model, is a document proposal in which the manager can explain how the planning and budget goals for the year were implemented and materialized into public policies that reach their recipients. Social engagement is an important tool to motivate managers to use public resources in actions in favor of the environment.